Incidence of the phoma leaf blight in drip irrigated coffee trees under different irrigation managements - Santos, Leone Stabile Dias; Pozza, Edson Apélio; Faria, Manoel Alves de; Silva, Mirian de Lourdes Oliveira e; Custódio, Adriano Augusto de Paiva; Vasco, Gabriel Brandão; Castro, Bárbara Mirelli de Melo e (Coffee Science - ISSN 1984-3909, 2014)
The knowledge that the disposition of the crop and the irrigation management affect the microclimatic conditions is of importance for the sampling and quantification of diseases, assisting in the achievement of a better management of the crop. This work aimed at evaluating the influence of drip irrigation management in the incidence of phoma leaf blight (Phoma tarda (R.W. Stewart) H. Verm.) on coffee trees, regarding the northern and southern exposed sides of the plants. The disease was evaluated between the years 2009 and 2011, on Acaiá coffee tree, planted in lesser distance between plants. A completely randomized block design was used, in a factorial scheme (5 irrigation managements x 2 exposure sides x 12 evaluation months) and 4 replicates, matching the treatment to the irrigation of the coffee trees in different conditions of water availability in the soil. The treatments non irrigated and irrigated throughout the whole year every time the availability factor of water was at most 0,75. The area under the disease progress curve, submitted to variance analysis for the qualitative analysis. In 2010/2011 the incidence of the disease was larger than in the first year. Larger incidences of the disease occurred in managements A and B. Plants that undergo a larger water stress become susceptible to infection by the pathogen. Interactions occurred between the time of the year with the exposure sides in the intensity of the disease, in which the disease occurred more intensely in the southern side in the first year and more intensely in the northern side in the second year. The largest progress of the disease occurs from April to August, during drier times.